Is there any Constraints?

Algebra Level 4

The coefficients of three consecutive terms of ( 1 + x ) n + 5 { \left( 1+x \right) }^{ n+5 } are in the ratio 5 : 10 : 14 5 :10: 14 . What is the value of n n ?

Details and Assumptions :

It need not be the first three consecutive terms.


The answer is 6.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

3 solutions

Chew-Seong Cheong
Oct 21, 2014

Let m = n + 5 m = n+5 and the three coefficients be given by:

( m r 1 ) : ( m r ) : ( m r + 1 ) = 5 : 10 : 14 \left( \begin{matrix} m \\ r-1 \end{matrix} \right) : \left( \begin{matrix} m \\ r \end{matrix} \right) : \left( \begin{matrix} m \\ r+1 \end{matrix} \right) = 5:10:14

m ! ( r 1 ) ! ( m r + 1 ) ! : m ! r ! ( m r ) ! : m ! ( r + 1 ) ! ( m r 1 ) ! = 5 : 10 : 14 \Rightarrow \dfrac {m!}{(r-1)!(m-r+1)!} : \dfrac {m!}{r!(m-r)!} : \dfrac {m!}{(r+1)!(m-r-1)!} = 5:10:14

( r 1 ) ! ( m r + 1 ) ! r ! ( m r ) ! = 2 m r + 1 r = 2 m = 3 r 1 . . . ( 1 ) \Rightarrow \dfrac {(r-1)!(m-r+1)!} {r!(m-r)!} = 2 \quad \Rightarrow \dfrac {m-r+1} {r} = 2 \quad \Rightarrow m = 3r -1 \space ...(1)

Similarly,

r ! ( m r ) ! ( r + 1 ) ! ( m r 1 ) ! = 7 5 m r r + 1 = 7 5 5 m = 12 r + 7 . . . ( 2 ) \Rightarrow \dfrac {r!(m-r)!} {(r+1)!(m-r-1)!} = \dfrac {7}{5} \quad \Rightarrow \dfrac {m-r} {r+1} = \dfrac {7}{5} \quad \Rightarrow 5m = 12r+7 \space ...(2)

Equation 1 × 5 1 \times 5 and equate it with equation 2 2 :

5 m = 15 r 5 = 12 r + 7 r = 4 m = 11 n = 6 5m = 15r - 5 = 12r +7 \quad \Rightarrow r = 4 \quad \Rightarrow m = 11 \quad \Rightarrow n = \boxed{6}

Let the three consecutive terms whose coefficients are in the ratio 5 : 10 : 14 be the ( r 1 ) t h (r-1)^{th} , ( r ) t h (r)^{th} and ( r + 1 ) t h (r+1)^{th} term respectively:

We know that in the expansion of ( 1 + x ) n (1+x)^n , the general formula for r t h r^{th} term is:

T r + 1 T_{r+1} = n C r C_{r} . x r x^{r}

The question here is similar:

Thus,

T ( r 2 ) + 1 T_{(r-2)+1} = (n+5) C r 2 C_{r-2} . x r 2 x^{r-2} (eq.1)

T ( r 1 ) + 1 T_{(r-1)+1} = (n+5) C r 1 C_{r-1} . x r 1 x^{r-1} (eq.2)

T r + 1 T_{r+1} = (n+5) C r C_{r} . x r x^{r} (eq.3)

From, eq. 1,2 and 3 we get that the coefficients of the three consecutive terms are:

(n+5) C r 2 C_{r-2} , (n+5) C r 1 C_{r-1} and (n+5) C r C_{r} respectively.

taking two coefficients at a time, namely from eq.1 and 2 , eq.2 and 3, we get..

( n + 5 ) ! ( r 2 ) ! . ( n + 5 r + 2 ) \frac{(n+5)!}{(r-2)!.(n+5-r+2)} / ( n + 5 ) ! ( r 1 ) ! . ( n + 5 r + 1 ) \frac{(n+5)!}{(r-1)!.(n+5-r+1)} = 5/10

( n + 5 ) ! ( r 1 ) ! . ( n + 5 r + 1 ) \frac{(n+5)!}{(r-1)!.(n+5-r+1)} / ( n + 5 ) ! ( r ) ! . ( n + 5 r ) \frac{(n+5)!}{(r)!.(n+5-r)} = 10/14

after, solving the two equations we get that :

r= ( n + 9 ) 3 \frac{(n+9)}{3} and 24r = 10n+60

substitute the value of r in latter eq., u will get that n = 6 \boxed{n=6}

Matt O
Nov 22, 2015

The coefficients of ( 1 + x ) n + 5 (1+x)^{n+5} are given by the (n+5)th row in Pascal's Triangle. Consider how the nth row is constructed - Each element can be described in terms of the previous term as follows: start with 1, then multiply by n and divide by 1 to get the next term, then repeat by multiply by 1 less and dividing by 1 more than in the previous step.

t 0 = ( n 0 ) = 1 t 1 = ( n 1 ) = t 0 n 1 t 2 = ( n 2 ) = t 1 n 1 2 e t c . . . t_0 = \binom{n}{0} = 1 \\ t_1 = \binom{n}{1} = t_0 \cdot \frac{n}{1} \\ t_2 = \binom{n}{2} = t_1 \cdot \frac{n-1}{2} \\ etc ...

For the 3 terms of interest, let j and k be the multiplying and dividing factors used to get the second term from the first. Using this method, this means j-1 and k+1 are the multiplying and dividing factors used to get the third term from the second. Therefore,

j k = 10 5 = 2 j = 2 k j 1 k + 1 = 14 10 = 7 5 5 j 5 = 7 k + 7 \frac{j}{k} = \frac{10}{5} = 2 \Rightarrow j = 2k \\ \frac{j-1}{k+1} = \frac{14}{10} = \frac{7}{5} \Rightarrow 5j - 5 = 7k + 7

Substitute the first equation into the second to get k = 4, j = 8

Reversing the method above, we get t 1 t_1 = 11. This means we're in the 11th row of Pascal's Triangle ( 1 + x ) n + 5 = ( 1 + x ) 11 n + 5 = 11 n = 6 (1+x)^{n+5} = (1+x)^{11} \Rightarrow n+5=11 \Rightarrow \boxed{n=6}

In summary, use a little intuition and get some easier equations to solve for.

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...